Endoscopic Therapy of Barrett’s Esophagus and Early Esophageal Adenocarcinoma - Leggett, Cadman L. (2013)
Endoscopic therapy of Barrett’s esophagus is feasible and likely to decrease the future risk of development of esophageal adenocarcinoma. The most commonly utilized therapy is radiofrequency ablation that has been shown to produce reproducible superficial injury in the esophagus. Other thermal therapies have been performed including multipolar coagulation, argon plasma coagulation, and thermal laser therapy. The other end of the ablative spectrum includes cryotherapy which involves freezing tissue to produce mucosal necrosis. Finally, photodynamic therapy has been used to photochemically eliminate abnormal mucosa. Endoscopic therapy has been demonstrated to be effective in high-risk situations such as Barrett’s esophagus with high-grade dysplasia. Even after the development of early esophageal carcinoma, endoscopic therapy is feasible so long as there are no risk factors for potential metastasis. Although the biological principles of re-epithelialization have not been well elucidated, it appears that adequate control of gastroesophageal reflux is necessary. There is a substantial risk of recurrence even after complete ablation that necessitates continued surveillance after ablation.